2021
DOI: 10.1371/journal.pone.0261349
|View full text |Cite
|
Sign up to set email alerts
|

Night shift work and the risk of metabolic syndrome: Findings from an 8-year hospital cohort

Abstract: Objectives Studies concerning the risk of metabolic syndrome associated with night work have shown inconsistent findings, due to imprecise working time data and cross-sectional design. We used register-based daily working time data to examine the risk of incident metabolic syndrome associated with night shift work. Methods Working time data collected between 2010 and 2018 of 5775 Taiwanese hospital workers were used to identify night shift workers and to calculate the number of night shifts. Metabolic syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…A study involving Malaysian manufacturing workers identified night shift work as a significant risk factor for MetS [ 10 ]. Research on Taiwanese hospital employees and railway workers in southwest China indicated that long-term shift work, particularly, heightened the risk of developing MetS [ 29 , 30 ]. A meta-analysis conducted in 2021 also indicated a positive correlation between shift work and the risk of MetS, which remained significant regardless of adjusting for sleep duration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study involving Malaysian manufacturing workers identified night shift work as a significant risk factor for MetS [ 10 ]. Research on Taiwanese hospital employees and railway workers in southwest China indicated that long-term shift work, particularly, heightened the risk of developing MetS [ 29 , 30 ]. A meta-analysis conducted in 2021 also indicated a positive correlation between shift work and the risk of MetS, which remained significant regardless of adjusting for sleep duration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shift workers commonly have inefficient and poor quality sleep causing fatigue ( Paech et al , 2010 ). Moreover, forced activity and sleep deprivation in the normal rest phase strongly impacts the immune system ( Irwin et al , 2006 ), and shift workers are more likely to develop chronic medical conditions like cardiovascular diseases ( Ha and Park, 2005 ), metabolic syndrome ( Cheng et al , 2021 ), psychological disorders (reviewed by Cheng & Drake, 2018 ) and others. Simulations of shift work and abnormal LD cycles in laboratory settings are used to investigate the mechanisms of chronodisruption and will be described in detail in the next sections.…”
Section: From a Circadian-resonant To A Chronodisrupted Health Statementioning
confidence: 99%
“…Shift workers commonly have inefficient and poor quality sleep causing fatigue (Paech et al, 2010). Moreover, forced activity and sleep deprivation in the normal rest phase strongly impacts the immune system (Irwin et al, 2006), and shift workers are more likely to develop chronic medical conditions like cardiovascular diseases (Ha and Park, 2005), metabolic syndrome (Cheng et al, 2021), psychological disorders (reviewed by P. Cheng & Drake, 2018) and others. Simulations of shift work and abnormal LD cycles in laboratory settings are used to investigate the mechanisms of chronodisruption and will be described in detail in the next sections.…”
Section: Levels Of Organization Of the Mammalian Circadian Clock Systemmentioning
confidence: 99%